2015
DOI: 10.1177/0021955x14566211
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of effective thermal conductivity of polymer matrix composite foams with biaxially aligned filler networks

Abstract: Recent research revealed potentials to develop polymer matrix composite foams filled with thermally conductive filler network as light-weight thermal management materials. Since polymeric foams are commonly used for thermal insulation, the concept of thermally conductive polymer matrix composite foams seems to be counter-intuitive, and the underlying factors that govern polymer matrix composite foam's effective thermal conductivity (k eff ) were not clear. In this context, this paper develops new models to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In actuality, the underlying mechanisms governing the conductivity of foamshow the solid (unfoamed) polymer and the gases entrapped in the cells contribute to the composite conductivity of the foam as a whole -are more complex, and are found to be different for open-celled and closed-celled foams. [104][105][106][107][108][109][110][111][112] These mechanisms may be further impacted by the presence of additives and the crystalline orientation of the polyolefin during foaming. 11,23,82,106,107 Several theoretical and empirical models that have been proposed to predict the thermal conductivity of multi-material systems -including series and parallel, Russel and Maxwell 109 and other models 106,[110][111][112] -may be employed to understand the thermal conductivity of foams.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In actuality, the underlying mechanisms governing the conductivity of foamshow the solid (unfoamed) polymer and the gases entrapped in the cells contribute to the composite conductivity of the foam as a whole -are more complex, and are found to be different for open-celled and closed-celled foams. [104][105][106][107][108][109][110][111][112] These mechanisms may be further impacted by the presence of additives and the crystalline orientation of the polyolefin during foaming. 11,23,82,106,107 Several theoretical and empirical models that have been proposed to predict the thermal conductivity of multi-material systems -including series and parallel, Russel and Maxwell 109 and other models 106,[110][111][112] -may be employed to understand the thermal conductivity of foams.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…In actuality, the underlying mechanisms governing the conductivity of foams – how the solid (unfoamed) polymer and the gases entrapped in the cells contribute to the composite conductivity of the foam as a whole – are more complex, and are found to be different for open-celled and closed-celled foams. 104112 These mechanisms may be further impacted by the presence of additives and the crystalline orientation of the polyolefin during foaming. 11,23,82,106,107…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leung et al [ 13 ] reported the effects of foam volume expansion and cell size on the λ value of resultant polyethylene (PE)/hBN foams. Besides, there are literatures dealing with the theoretical work of filler included in PTCs [ 9 , 14 ]. Although notable experimental and theoretical progress have been made in this area, the obtained thermal conduction abilities of PTCs are still far away from meeting industrial applications needs.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, foaming-induced extensional stress field was used to align thermally conductive filler in polymer composites to increase their k eff . [14][15][16] This promote the formation of a three-dimensional thermally conductive network throughout the bulk material. Ghariniyat et al integrated this technique and post-foaming elastic recovery of thermoplastic polyurethane to fabricate flexible thermally conductive TPU-hexagonal boron nitride (hBN) composites.…”
mentioning
confidence: 99%